Karpacz w oczach mieszkańców i turystów - analiza porównawcza wizerunków - Adamczuk, Franciszek (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
The paper aims at showing the main elements and factors shaping image of Karpacz city, well recognized tourist destination in Poland and abroad. The town has adopted clear development goals that boil down to active promotion of local resources and formulation of tourist product. The article also addresses the issue of similarities and differences of image perceived by city dwellers and tourists. Drawn conclusions are based on field research (232 respondents) conducted between 2001 and 2005, and as such could be used as a tool for shaping tourist functions of the city as well as the region. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Gospodarka a Środowisko (6); 2006; nr 1145, s. 201-212